Multilingual issues in Nordic mathematics education – What is achieved and where to go next? - Prediger, Susanne (NOMAD Nordic Studies in Mathematics Education, 2018)
This Nomad special issue provides eleven highly interesting insights into current research and development projects in mathematics education on multilingual and multicultural issues. It shows the diversity of approaches currently adopted in the Nordic Countries with an impressing richness of perspectives and ideas. I am grateful to have had the opportunity to read and discuss the papers carefully as I learned a lot. In this commentary, I compare and connect the papers with each other and the international state of research and to suggest some directions for further research and deve-lopment. The commentary is structured in the following steps: Different implicit and explicit conceptualization of languages are identified in the articles (first section); different research approaches are summarized with a need to strengthen Design research (second section); and different instructional approaches for activating multiple language resources for mathematics learning and further enhancing both languages (third section).